Shock Reduction Technique in Thin-Plate Structure Using Elastic Patches with Gradual Thickness Variations - Hyun-Su Park; Dae-Hyun Hwang; Jae-Hung Han (Shock and Vibration)
Reducing structural shocks propagated as elastic waves in thin plate-like structures is of paramount importance in diverse engineering applications. In this study, a shock reduction method using elastic patches that deflect bending waves through wave refraction, while maintaining the structural stiffness and strength is presented. Elastic patches with gradual thickness variation were designed and thoroughly investigated both numerically and experimentally. Two types of triangular elastic patches, flat and pyramid-shaped, were utilized to refract and attenuate transient bending waves at different incident angles. All results from ray tracing, finite element analysis, and experiments consistently demonstrated the effective reduction of passing waves in areas behind the attached patches. Moreover, the influence of gradual thickness variation was thoroughly discussed. The proposed method provides a practical approach to mitigate transient shock responses in specific target areas across various structural applications without compromising structural stiffness and strength.